HOXC9: a key regulator of endothelial cell quiescence and vascular morphogenesis - Cramer-Stoll, Sandra; Kroll, Jens (Trends in cardiovascular medicine, 2012)
The members of the HOX transcription factor family are important basic regulators of morphogenesis and development and several HOX proteins have also been identified as essential regulators of physiological and pathologic angiogenesis. HOXC9 is highly expressed in quiescent endothelial cells and keeps the vasculature in a resting state via inhibition of interleukin-8 production. HOXC9 overexpression in zebra-fish negatively regulated vascular development which can be rescued by exogenous interleukin-8. The further understanding of the HOXC9-IL-8 signaling axis and the identification of other HOXC9 targets in the vasculature will provide important insights into mechanisms promoting endothelial cell activation during physiological angiogenesis. It will also be beneficial to understand pathophysiological angiogenesis regulation and thus provide important new directions for the development of novel anti-angiogenic therapeutic strategies.